Design of Occupational Health and Safety Management Information System at Telogorejo Semarang Hospital (Unnes Journal of Public Health, 2020)
Hospital is one company that is required to develop hospital OHS Management System. Hospital OHS management System is required to carry out the process of recording and reporting OHS which is integrated with the hospital management information system. Problems that occur in the recording and reporting system include difficulties in accessing and searching data, inaccurate in inputting, processing and presenting data, susceptible to data loss, and incomplete information produced. The purpose of this study was to develop an OHS Management Information System at Telogorejo Hospital, Semarang, and test the system. The system design is built based on the stages in the Waterfall Method namely Requirement Analysis, System Design, Implementation, and Testing using the Blackbox Method. The results of this study are the establishment of the Hospital’s OHS Information System which is able to produce output in the form of reports and graphs, and the system has worked well and correctly as expected and in accordance to the rules outlined by the system users and is able to accommodate multi-user use. The conclusion of this study is that the use of the Hospital’s OHS Information System can simplify the data input and process, speed up data searching, and produce more accurate outputs.